On Zorich maps and other topics in quasiregular dynamics - Tsantaris, Athanasios (2022)
The work in this thesis revolves around the study of dynamical systems arising from iterating quasiregular maps. Quasiregular maps are a natural generalization of holomorphic maps in higher (real) dimensions and their dynamics have only recently started being systematically studied.